Non-destructive chemical analysis of water and chlorine content in cement paste using near-infrared spectroscopy. (30th January 2019) - Watanabe, A.; Furukawa, H.; Miyamoto, S.; Minagawa, H.
Graphical abstract: Highlights: To investigate if NIR spectroscopy can assess water and chloride ion content in cement paste. Absorption peak intensities of the OH group increased as moisture content rose. Absorption peak intensities of Friedel's salt increased with higher chloride content. Quantitative analysis with NIR spectroscopy possible for ordinary Portland cement. Abstract: Chloride induced deterioration of concrete structures is well underway when the damage is visually detected during inspection. If such damage was identified using a non-destructive method, inspection costs would reduce significantly. We tested the use of near-infrared (NIR) spectroscopy for non-destructive multicomponent analysis of cement pastes. Cement paste samples with varying chloride-ion concentrations and humidity were prepared for different cement types. Reflectance spectra were obtained, then total moisture content (v/v) and chloride ion concentrations were measured using destructive testing as a reference. A correlation was observed between the measured water amount/chloride ion concentration and respective NIR absorption values.